Early Marriage and Maternal Anxiety in Caring for Sick Children in Primary Healthcare Settings - Kiki Rokhmawati Azizah; Ahmad Kholid Fauzi; Tasrip Tasrip (Genius Publishing (CV. Gerbang Ilmu Nusantara), 2025)
Introduction: Early marriage is often associated with psychological immaturity, which may affect an individual’s ability to cope with stressful situations, including caring for a sick child. Limited emotional readiness may increase the risk of anxiety among young couples when facing child health problems.Objectives: This study aimed to analyze the effect of early marriage age on anxiety levels in caring for sick children.Methods: This study employed an analytic correlational design with a cross-sectional approach. A total of 140 respondents were included using a total sampling technique. Data were collected using structured questionnaires and analyzed using the Spearman rank correlation test with a significance level of p < 0.05.Results: The findings showed a statistically significant relationship between early marriage age and anxiety levels (p = 0.001). The correlation coefficient (r = -0.531) indicated a moderate negative relationship, suggesting that younger age at marriage is associated with higher levels of anxiety in caring for sick children.Conclusions: Early marriage age has a significant influence on anxiety levels in caring for sick children. These findings highlight the importance of psychological readiness and maturity in family life, particularly in managing stress related to child health.